No particle production in two dimensions: recursion relations and multi-Regge limit - Gabai, Barak; Mazáč, Dalimil; Shieber, Andrei; Vieira, Pedro [UNESP]; Zhou, Yehao (Springer Nature, 2019)
We introduce high-energy limits which allow us to derive recursion relations fixing the various couplings of Lagrangians of two-dimensional relativistic quantum field theories with no tree-level particle production in a very straightforward way. The sine-Gordon model, the Bullough-Dodd theory, Toda theories of various kinds and the U(N) non-linear sigma model can all be rediscovered in this way. The results here were the outcome of our explorations at the 2017 Perimeter Institute Winter School.
Keywords: Field Theories in Lower Dimensions; Integrable Field Theories; Scattering Amplitudes